Critical depth prediction based on in-situ stress and gas content model of deep coalbed methane in Liupanshui Coalfield in China - Fang Lv; Ruidong Yang; Wei Gao; Lingyun Zhao; Yaohui Liu; Zhihua Yan; Fulun Shi; Binxin Zhang; Jingui Tang; Tongsheng Yi (Scientific Reports)
Abstract In-situ stress plays a pivotal role in influencing the desorption, adsorption, and transportation of coalbed methane. The reservoir gas content represents a pivotal physical parameter, encapsulating both the coalbed methane enrichment capacity and the underlying enrichment law of the reservoir. This investigation collates, computes, and consolidates data concerning pore pressure, breakdown pressure, closure pressure, triaxial principal stress, gas content, lateral pressure coefficient, and other pertinent variables from coal reservoirs within several coal-bearing synclines in the Liupanshui coalfield, China. This study elucidates the characteristics of longitudinal stress development in the study area, the gas content of the longitudinal reservoirs and their interrelationships. The study area is situated within the middle-high stress zone, exhibiting discernible evolution patterns from reverse fault mechanism to strike-slip fault mechanism to normal fault mechanism, progressing from shallow to deep. In the deeper stratigraphy, a strike-slip-normal fault mechanism emerges. The relationship between burial depth and triaxial principal stress is subjected to linear regression, resulting in the proposal of a simplified model for vertical in-situ stress. The hyperbolic regression algorithm was employed in order to derive both the envelope and median formulas for lateral pressure coefficient (k values). The k value displays discrete behavior along the vertical axis in shallow depths, gradually converging in deeper strata and ultimately stabilising at approximately 0.65 with increasing depth. A comprehensive examination of the k value substantiates the efficacy of the simplified in-situ stress model along the vertical axis, offering profound insights into the vertical interrelationships and evolving patterns of the triaxial principal stresses. The mean gas content in the study area was found to be 11.89 m³/t, exhibiting a general increase in depth, followed by a subsequent decrease. The pore pressure (P p) displays a discernible positive correlation with gas content. This study comprehensively elucidates the developmental patterns of the stress field, the simplified model of vertical in-situ stress, the attributes of the stress ratio (K H, k h, lateral pressure coefficient k), the characteristics of reservoir gas content, and the corresponding and transformative relationships between coupled geostress field parameters and gas content. The lateral pressure coefficient conversion depth, in-situ stress conversion depth, and gas inversion depth are delineated, accompanied by a detailed exposition of their definition process, physical significance, and interrelations. Within the study area, the lateral pressure coefficient conversion depth is estimated to range between 450 and 500 m, while the critical depth for in-situ stress conversion is approximately 670 m. Moreover, the critical depth for gas content conversion falls within the range of 700–800 m. It is noteworthy that the critical depth for deep coalbed methane within the Liupanshui coalfield has been identified as approximately 800 m. Subsequently, a vertical “in-situ stress-gas content mode” relationship model for coalbed methane development was formulated, thereby providing a structured framework for understanding the dynamic interactions between vertical in-situ stress and gas content.